2022
DOI: 10.1111/iwj.13783
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical efficacy of a dressing with a soft cellulose fluff core in protecting prone surgical patients from chest injuries on the operating table

Abstract: Pressure ulcers are soft-tissue damage associated with tissue exposure to sustained deformations and stress concentrations. In patients who are proned for ventilation or surgery, such damage may occur in the superficial chest tissues that are compressed between the rib cage and the support surface. Prophylactic dressings have been previously proven as generally effective for pressure ulcer prevention. In this study, our goal was to develop a novel computational modelling framework to investigate the biomechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In our previous study on the Relton‐Hall frame, which is used to fix the body in the prone position during posterior spinal surgery, we reported that SMD was more effective than film dressing in preventing IAPIs 20 . A dressing with a soft cellulose fluff core distributes stress concentrations to the chest in surgical patients prone on the surgical table 21 . One of the primary PIs prevention should be for minimising deformations by either reducing the peak strain/stress values in tissues 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study on the Relton‐Hall frame, which is used to fix the body in the prone position during posterior spinal surgery, we reported that SMD was more effective than film dressing in preventing IAPIs 20 . A dressing with a soft cellulose fluff core distributes stress concentrations to the chest in surgical patients prone on the surgical table 21 . One of the primary PIs prevention should be for minimising deformations by either reducing the peak strain/stress values in tissues 11 .…”
Section: Discussionmentioning
confidence: 99%
“… 20 A dressing with a soft cellulose fluff core distributes stress concentrations to the chest in surgical patients prone on the surgical table. 21 One of the primary PIs prevention should be for minimising deformations by either reducing the peak strain/stress values in tissues. 11 SMD is recommended as a prophylactic dressing in AORM guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of a wider application of cellulose-based materials as a new type of absorbents or fillers are related to their abundance, low cost, easy recycling, and biocompatibility. These properties are of special interest for application in different practical fields such as environmental protection [1,2], energy storage [3], garment design [4], surgical pads [5], wound healing [6][7][8], absorbent hygiene products [9], pharmaceuticals [10][11][12], and 3D printing [13]. Cellulose-based gels are also studied as future materials for food packaging and plant agriculture [14], antimicrobial [15], and electroactive [16] materials.…”
Section: Introductionmentioning
confidence: 99%